THE IMPLEMENTATION OF ICT APPS IN SPEAKING CLASS - Awwaliyah, Andi Astri; Noni, Nurdin; Amin, Fatimah Hidayahni; Adys, Himala Praptami; Mohamad, Andi Riswan (Universitas Negeri Makassar, 2024)
This study aims to explore how the implementation of ICT apps influences students’ engagement in speaking class. In the current digital era, ICT apps have become an integral part of education. However, it remains unclear how the use of ICT apps affects students’ engagement in speaking class. Therefore, the objective of this study is to investigate the implementation of ICT apps on students’ engagement in speaking class. Qualitative research with a descriptive design was adapted in this study. The participants were students of the English Education Study Program, Universitas Negeri Makassar. Through a purposive sampling technique, the lecturer and students of Class A were selected as the research participants. The instruments used were observation checklists and notes to collect the data. The researchers used three steps to analyze the data, there were data reduction, data display, drawing and verifying conclusion. The research findings revealed lecturer plays a crucial role in facilitating engagement by providing challenging tasks and opportunities for students to express themselves. Ultimately, high levels of students’ engagement not only contribute to individual learning outcomes but also foster a sense of validation within the university community, promoting broader talent development and interaction among students and staff. This study concluded that the lecturer plays a crucial role in encouraging engagement by providing challenging tasks. Based on the findings of this study, it is recommended that students assist themselves and their peers in learning speaking with ICT apps. Lecturers can utilize ICT apps in the English teaching and learning process effectively, thus improving the quality of education and preparing students with updated knowledge to adapt to the changing world. Additionally, other researchers can use this study as a reference for recommending study material to increase insight and conduct studies related to the implementation of ICT apps in the speaking class.